Emerin deficiency does not exacerbate cardiomyopathy in a murine model of Emery–Dreifuss muscular dystrophy caused by an LMNA gene mutation - Eiji Wada; Kohei Matsumoto; Nao Susumu; Megumi Kato; Yukiko K. Hayashi (Journal of Physiological Sciences)
Abstract Emery–Dreifuss muscular dystrophy (EDMD), caused by mutations in genes encoding nuclear envelope proteins, is clinically characterized by muscular dystrophy, early joint contracture, and life-threatening cardiac abnormalities. To elucidate the pathophysiological mechanisms underlying striated muscle involvement in EDMD, we previously established a murine model with mutations in Emd and Lmna (Emd −/−/Lmna H222P/H222P; EH), and reported exacerbated skeletal muscle phenotypes and no notable cardiac phenotypes at 12 weeks of age. We predicted that lack of emerin in Lmna H222P/H222P mice causes an earlier onset and more pronounced cardiac dysfunction at later stages. In this study, cardiac abnormalities of EDMD mice were compared at 18 and 30 weeks of age. Contrary to our expectations, physiological and histological analyses indicated that emerin deficiency causes no prominent differences of cardiac involvement in Lmna H222P/H222P mice. These results suggest that emerin does not contribute to cardiomyopathy progression in Lmna H222P/H222P mice.